Pengembangan Media Pembelajaran Interaktif Berbasis Power Point Pada Tema 1 Subtema 3 Pertumbuhan Hewan Kelas III SDN 36 Pontianak Selatan - Kinanty, Putri; Kartono, Kartono; Salimi, Asmayani (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2024)
The research carried out aims to develop media products in learning activities in the form of power point-based interactive learning media created for thematic learning in theme 1 sub-theme 3 class III at SDN 36 South Pontianak which meets the requirements to assist teaching and learning activities in the 2013 curriculum This research method is the R&D method with the ADDIE development model. This research data involved 26 class III B students at SDN 36 South Pontianak, 1 media expert validator and a material expert. The data collection technique in this research is observation and questionnaires. The results after the research show that the process of developing interactive power point-based learning media on theme 1, sub-theme 3, animal growth, class III, SDN 36 South Pontianak has gone through five stages of the ADDIE model research. Validity activities for PowerPoint-based learning media products produced very good criteria with an average score of 93.33% for the media aspect, 95.45% for the material aspect. Then get an average score of 97.78% for student responses to learning media. So this PowerPoint-based interactive learning media is suitable to be used and tested.